The Role of Servicescape and Perceived Sacrifice on Loyalty Intentions University Students - Wilma Cordelia Izaak; Ronggo Alit (Nusantara Science and Technology Proceedings)
This research aims to examine the important role of the servicescape on the level of commitment of college students to complete their lectures at their university. This research also tries to explain how perceived sacrifice in moderating servicescape towards intention to be loyal from new state university students. By using Partial Least Square analysis, the results are expected to be able to show the role of the servicescape towards the intention to be loyal to students and with student’s perceived sacrifice able to strengthen or weaken student judgment to servicescape. This research is only carried out in a limited scope, where the population is students of 2016 until 2018 so that they can still pass the disposition stage or switch to different decisions during their study so that the focus of the research is students of class 2016 until students of class 2018 who are still actively recorded on the main data of the faculty. The main reason for this population selection is to get measurable results whether there is a relationship to the assessment of servicescape with loyalty intentions, with the moderator variables of student’s perceived sacrifice. The results of this research are expected to be able to provide a new choice that enriches the process of developing service marketing in good university governance for higher education and the learning process for all parties. Within the examination among research variables, it was found that servicescape and perceived sacrifice have a significant effect on the implementation of student loyalty intentions. The results of this study can be used as a reference for the improvement of good university government construction management using a sustainable servicescape approach among students.